Alegorias do estado autoritário em o pagador de promessas e em o santo inquérito - Gomes, Robson Teles (2014)
The allegorical concept of an Authoritarian State is discussed in some areas of knowledge, including History and Social Science. As a field of knowledge that reproduces "realities" discussed in these areas, Literature can be an area of tension between these two discursive representations and relates to allegorical socio-historical creations facts, in research of a resignification of such facts, as the allegory metamorphoses itself the language and the content of a speech, by saying one thing but meaning another. In this sense, in O Pagador de Promessas and in O Santo Inquérito, Dias Gomes, the experiences undergone by these characters Zé-do-Burro - a country man - and Branca Dias a new Christian represents allegories of a Brazilian historic moment. Thus, to better understand this allegorization, in the first moment, it exposes a panoramic vision of the alleged evolution of the concept of allegory and a brief course of the nation concept. Such behavior anticipates the main theoretical procedures adopted in this work, called by Fredric Jameson of National Allegory. In the second moment, there is a historical contextualization of environments of the 1960s, with the aim of drawing attention to a dictatorial environment by which Brazil went, in addition to observe that, in these parts, the playwright proposes rewriting certain times in the History of the country through conflict and dramatic actions. For both, the allegorical language was - and has been - one of the tools more applicants. This is the profile that is configured in the two plays of Dias Gomes that this research proposes highlight.